SIMULATION OF COAL HANDLING PLANT TO SUPPORT THE STABILITY OF COAL SUPPLY - KUSMIWARDHANA, DANANG; Sugiono, Sugiono (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2020)
PLTU PJB UPJ O&M Paiton is a steam power plant which uses coal as a fuel Coal Handling Plant. It is an important unit to control coal supply. Recently, PLTU PJB UPJ O&M Paiton uses coal from many suppliers. That suppliers can be devided in two qualities based on they calorific values, which low rank and high rank. Multi supplier can affect instability of boiler performance if the coal supply to boiler didn’t managed properly. The blending process between high rank coal and low rank coal had been done to solve that problem, but unwanted mixing between supplier still can be happened if there is not proper management in the coal yard.The solution offered to solve the problem is by making design lost to district from actual system, So that, it is necessary to ascertain how the impact of lost to system in CHP. Simulation method is used to know that impact. The simulation is done with EXTEND6TM software by modeling the components of the existing CHP system.